PENGELOLAAN WAKAF SEBAGAI SARANA PENINGKATAN STRATEGI EKONOMI UMAT - Ghozali, Mohammad; Annas, Muhamad (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
Waqf is one of the instruments in the sharia economy that has the potential to improve the welfare of the community. As an economic instrument waqf also plays a role to support various productive activities and redistribution of welfare to underprivileged communities and play a role in the development of the social, economic, and cultural life of the community. Also, in Islam waqf becomes a more expensive instrument to invite its managers to have an entrepreneurial spirit where waqf assets as capital and the result of the management of waqf property is used for the economic development of the community. This study aims to find out how waqf management strategy and how the role of waqf in improving the economy of the people. The study methodology used is the qualitative method. The results obtained in this study that the strategy in its management such as determining the standard of professionalism nazir because nazir has an important role in the management of waqf. Counseling the community so that the community better understands waqf is not only limited to waqf inanimate objects. Issued a law that discusses in full waqf both in terms of procurement, management, and distribution of the results of the management of the waqf so that the waqf can be a means of improving the economy of the people. And the establishment of a professional national waqf institution that is ready to supervise every development of waqf. Waqf has a role in strengthening brotherhood in the community as well as in the development of social life, economy, and culture of the community. Wakaf also serves as an instrument of public finance shari'ah which has great potential in generating financing for the State, improving the welfare of people, developing social, economic, and cultural activities of Islamic society.